Pecularities of shoulder joint arthroplasty after war injuries - S.S. Strafun; V.V. Gaiovych; O.S. Strafun; S.V. Bogdan; D.D. Kravchenko (Bolʹ, Sustavy, Pozvonočnik)
Background. Shoulder arthroplasty in patients after combat injuries is a complex and multicomponent problem. This study aimed to analyze our first experience of treating patients with gunshot and blast injuries with shoulder arthroplasty. Materials and methods. We observed 14 patients with the consequences of severe polystructural injuries of the shoulder joint due to shrapnel (12 subjects) and bullet (2 patients). Results. Shoulder joint arthroplasty was performed in 4 to 20 months after gunshot or blast injury (on average 9.4 months). A reverse shoulder arthroplasty was performed when only the deltoid muscle or the transplanted latissimus dorsi muscle was preserved (4 cases). In other cases, an anatomical unipolar system was used when the function of the deltoid muscle and rotator cuff muscles was preserved (6 patients). In cases of gunshot injuries of the glenoid and preserved muscles, a bipolar anatomical shoulder arthroplasty was performed (4 cases). In three patients who underwent transplantation of the active thoracodorsal muscle 12 months after arthroplasty, the function of the shoulder joint, according to the Constant Shoulder Score, ranged from 62 to 72 points (on average 67.7 points). Long-term results after anatomical arthroplasty were evaluated in 7 patients. The function, according to the Constant Shoulder Score after 12 months, ranged from 69 to 93 points (on average 81.1 points). The increase in shoulder function with anatomical arthroplasty was a bit higher, but the injury was also less severe. Conclusions. Shoulder joint replacement in patients with consequences of severe war wounds of the shoulder allows for restoring the painless active function of the shoulder joint. A background for successful restoration of movements in the shoulder joint in such patients is a meticulous assessment of the severity of damaged structures, the development of individual reconstruction strategy and adequate use of a wide range of endoprosthesis devices.